Waste energy recovery in window air conditioning system - Sasidharan, R.; Palaniswamy, V.; Manibharathi, C.R.; Pannerselvam, R.; Venkatesan, N. (International Journal of Engineering and Technology, 2014)
“Faster, mightier & smaller” is still the keyword for every invention and development. In day-to-day world we concentrate on the compactness and efficiency of every product. Keeping this in thought, the “Waste Energy Recovery in Window Air conditioning System” is designed and fabricated in an economical manner. “Human comfort is that condition of mind, which expresses itself with the thermal environment”. In this two rival properties of cool water and heat water are obtained. This system can be used continuously. By using this system there is no need of going for a separate air conditioner or water heater and water cooler. As both purposes are served by a single system, the cost is also lowered to a considerable level. Keywords: Waste Energy, Window Air Conditioning System.